2010
DOI: 10.2478/v10042-009-0050-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ovarian steroidogenesis and beta-endorphin in the Lizard Uromastyx acanthinura: Immunohistochemical approach.

Abstract: Abstract:In Mammals, opioid peptides are involved in various physiological processes including the reproductive function. The knowledge of the distribution of β-endorphin, one of opioid peptides in Reptiles ovaries is very limited. Therefore, the present study used the lizard ovarian follicles to further elucidate the role of this peptide in steroidogenesis. In Uromastyx acanthinura, the localization of both this peptide and sex steroid hormone was investigated by the immunohistochemical approach. This techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…(Barbosa-Moyano et al, 2020). ER, and PR presence was not related to the sex steroid concentrations, as reported in the lizard U. acanthinura (Hammouche et al, 2017).…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…(Barbosa-Moyano et al, 2020). ER, and PR presence was not related to the sex steroid concentrations, as reported in the lizard U. acanthinura (Hammouche et al, 2017).…”
Section: Discussionsupporting
confidence: 47%
“…In the previtellogenic phase, ERα in the small cells could be associated with the proliferative activity to differentiate in a polymorphic granulosa (Kocanova et al, 2010;Hamilton et al, 2017). Also, its presence in the cytoplasm of the pyriform cells may indicate their role in the estrogen stimulation synthesis and secretion in previtellogenic follicles (Hammouche et al, 2017;Fuentes and Silveyra, 2019), inducing aromatase activity at the beginning of the reproductive season (Tripathy and Rai, 2017). This steroidogenic capacity has been observed in the granulosa cells of previtellogenic and early vitellogenic follicles in S. torquatus (unpublished data).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In U. acanthinura female, our previous research confirmed the seasonal ovarian activity which running from Spring until Summer and the existence of one ovulatory clutch [1]. Several aspects of endocrine control of vitellogenesis have been observed in female [32][33][34][35][36], and male treated with 17b-estradiol obtained the ability to produce vitellogenin [37]. In order to determine the estrogen receptor subtypes and the progesterone receptor isoforms involved in the regulation of the synthesis of vitellogenin in U. acanthinura, we analyzed the presence of estrogen and progesterone receptors in the liver of wild females and females treated with 17b-estradiol using an immunohistochemical method.…”
Section: Introductionmentioning
confidence: 61%
“…A control of specificity consisted in omitting the primary antiserum step to test non-specific binding of secondary antibody to the tissue was performed. The primary antibodies were also tested in the U. acanthinura [35,38] and the rat Psammomys obesus ovaries [39].…”
Section: Immunohistochemical Analysismentioning
confidence: 99%